1998
DOI: 10.1056/nejm199806253382602
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Rectal Diazepam Gel and Placebo for Acute Repetitive Seizures

Abstract: Rectal diazepam gel, administered at home by trained care givers, is an effective and well-tolerated treatment for acute repetitive seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(195 citation statements)
references
References 30 publications
7
183
1
4
Order By: Relevance
“…Respiratory depression after rectal administration of diazepam in children was reported in five class III trials, ranging from 1.2 percent to 6.4 percent (35,41,42,45,47), while two class III trials (37,40) and two class I trials in acute repetitive seizures (59,60) reported no incidence of respiratory depression with rectal diazepam use in children. No respiratory depression was reported in one study of six children treated with rectal lorazepam (35).…”
Section: Pediatric Studiesmentioning
confidence: 99%
“…Respiratory depression after rectal administration of diazepam in children was reported in five class III trials, ranging from 1.2 percent to 6.4 percent (35,41,42,45,47), while two class III trials (37,40) and two class I trials in acute repetitive seizures (59,60) reported no incidence of respiratory depression with rectal diazepam use in children. No respiratory depression was reported in one study of six children treated with rectal lorazepam (35).…”
Section: Pediatric Studiesmentioning
confidence: 99%
“…A new form of treatment for acute seizure activity that may be used at home is diazepam administered in a rectal solution, but this is approved for use in selected refractory patients to control acute, repetitive seizure activity and is not used after a single unprovoked seizure. 64,65 Summary. Whereas evidence from studies of treatment after only a single unprovoked seizure is lacking, Class I and II evidence concerning the AED accepted for use as first-line anticonvulsants in children (PB, PHT, VPA, CBZ) indicates that clinically relevant cognitive and behavioral effects may occur, particularly with PB.…”
Section: What Are the Nature And Frequency Of Side Effects Of Aed Commentioning
confidence: 99%
“…[11][12][13][14][15][16] However, it requires a patient to be partially undressed, which can be viewed as problematic for the patient, school staff, and other students, especially in partially conscious students when there is no ready means of privacy to preserve the patient's dignity. Families may appreciate consultation about these issues before formulation and implementation of an action plan.…”
Section: Rectal Diazepam Gelmentioning
confidence: 99%